Relationship between Psychological well-being and Marital Conflicts among Parents with Down Syndrome Children - Riaz, Sidra; Ghauri, Tauqir Ahmad; Shinwari, Rizwan Ali; Masood, Arbab (Pakistan Journal of Humanities and Social Sciences, 2022)
The present study is conducted in Pakistan and will investigate the relationship between psychological well-being and marital conflicts among parents with Down syndrome children. The study was conducted in institutes of Islamabad, which include the Al-Farabi Institute and the National Institute of Rehabilitation Medicine. The study was conducted in the speech and physiotherapy department of institutes and included those patients who were suffering from Down syndrome. Purposive sampling was used to acquire the data from 60 parents (30 mothers and 30 fathers) of Down syndrome children. Regression and correlation analysis was performed to determine the link between independent and dependent variables as well as the impact of psychological well-being (autonomy, environmental mastery, purpose in life, personal growth, self-acceptance, and positive relations) on marital conflicts. The results show a positive and insignificant relationship between autonomy, positive relations, personal growth, self–acceptance, and marital conflicts but also reveal a negative and significant relationship between environmental mastery, purpose in life, and marital conflicts due to a poor environment. The research will help parents to lessen their stress and improve their environment. It will also guide the NGOs and civil society to encourage the parents and give them awareness about the coping strategies to deal with these situations.